Rancang Aplikasi Perpustakaan Digital Universitas PGRI Silampari Berbasis Mobile Dengan Metode Prototype - Lastri Sartika; Rahman Dzaky Faishal Ali; Tia Julita; M.Rizki Syawaldi (Proceeding of Silampari Conference of Life Science and Technology, 2026)
The acceleration of information technology in the contemporary digital epoch necessitates higher education institutions to undergo continuous transformation to reinforce the quality of academic services, particularly within library management systems as central hubs for literature. Currently, Universitas PGRI Silampari encounters significant operational hurdles in its conventional book circulation management. Primary challenges encompass physical storage constraints for collections, inefficient reference retrieval mechanisms, and accessibility barriers for students with high mobility. These circumstances directly result in diminished academic productivity and prolonged administrative processing durations. This research initiates the design and development of an innovative mobile-based digital solution titled